PBI-BuI and PAN-PSSALi based UF membranes: effects of solute and membrane surface interactions on rejection and flux - Bhagat, Deepti G.; Mule, Bhavana; Mandlekar, Neeraj; Pandare, Kiran; Kharul, Ulhas K. (Desalination, 2014)
Ultrafiltration membrane using tert-butylpolybenzimidazole (PBI-BuI) was prepared and characterized for flux and rejection performance using Gel Permeation Chromatography (GPC). Polyethylene glycol (PEG) and polyethylene oxide (PEO) with different molecular weights were used as the solutes. While using feed solution containing mixture of PEGs, higher rejection was observed than using individual PEG. The water flux of PBI-BuI membrane after passing individual PEG solutions showed considerable (similar to 36%) reduction, which could be attributable to the PEG adsorption on the membrane pore surface. PEG adsorption was further substantiated by SEM, IR and TGA. The amphoteric nature of PBI-BuI could cause H-bonding between membrane surface and PEG molecules, leading to PEG adsorption on the membrane and pore surface. To ascertain this postulation, a study with PAN-PSSALi (which does not contain H-bonding) based UF membrane containing negatively charged -SO3- group was done. It was found that PEG adsorption in this case is not as predominant as in earlier case. This membrane showed marginal reduction in water flux of 8%, vis-a-vis 36% reduction shown by PBI-BuI based membrane. This indicated that H-bonding present in PBI-BuI is mainly responsible for the PEG adsorption on its membrane and pore surface, in spite of PEG being a neutral molecule. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Polybenzimidazole; Rejection; Solute adsorption; Ultrafiltration